The Economic Costs of Trade Sanctions: Evidence from North Korea - Jihee Kim; Kyoochul Kim; Sangyoon Park; Chang Sun (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper investigates the economic costs of the recent United Nations sanctions on North Korea. Exploiting a novel data set on North Korean firms, we construct measures of regional exposure to export and intermediate input sanctions and show that trade sanctions cause sharp declines in local nighttime luminosity. Additional analysis of newly available product-level price data reveals that import sanctions led to significant increases in market prices. We then estimate a quantitative spatial equilibrium model using cross-region variations. The model implies that the sanctions reduced the country's manufacturing output by 12.9% and real income by 15.3%. We further quantify the potential impact of alternative sanction scenarios.
Keywords: F51; R11; O18; P20; 330; trade sanction; regional economy; spatial equilibrium; North Korea